Evoked craving in high-dose benzodiazepine users - Zamboni, Lorenzo; Benvegnù, Giulia; Fusina, Francesca; Vesentini, Roberta; Locatelli, Francesca; Mattiello, Matteo; Mannari, Vanessa; Campagnari, Simone; Toldo, Silvia; Congiu, Alessio; Brendolan, Maria; Verlato, Giuseppe; et al. (Frontiers in Psychiatry, 2025)
IntroductionBenzodiazepines (BDZs) are among the most abused substances worldwide, and high-dose BDZ abuse is considered a specific type of addiction. Cue reactivity (CR) is a hypersensitivity to motivational stimuli and, in substance use disorders, it increases craving and facilitates relapse, especially in chronic users. Virtual reality (VR) may be a viable technology to implement in CR paradigms. The general objective of this study is the implementation of a VR protocol to identify the causal relationship between the environmental features of a specific setting and craving responses in BDZ abusers.MethodsMoreover, we investigated the correlation between the degree of BDZ craving and measures of mood, affect, attention, sense of presence, and cybersickness in the subjects, and evaluated the effectiveness that different VR environments have in discriminating between BDZ abusers and controls by comparing the degree of BDZ craving and all of the aforementioned variables in the two groups.ResultsOur data suggest that cues can indeed become conditioned to elicit craving responses in high-dose BDZ abusers, but more studies are necessary to confirm this hypothesis.ConclusionMoreover, the use of VR can be a good choice to observe environmental craving for BDZs since it presents a realistic simulation of real-world settings.